Avaliação de desempenho multicritério como apoio à gestão de P&D do Programa Baja SAE Brasil: um estudo de caso na equipe Pato Baja, UTFPR - PB - Piovesani, Viviane (2017)
Research and development (R&D) projects have unique characteristics, singular to the projects to which they belong. Thus, the performance assessment should consider these features, that are complex, conflicting and uncertain. In this context, the present work aimed to build a performance evaluation model to support the R&D management of the Pato Baja project of the Federal Technological University of Paraná - Campus Pato Branco. The research is developed in two phases, the first bibliographical, as it builds the knowledge about evaluation of organizational performance for the management of R&D projects, through the selection of bibliographic portfolios and the analysis of their content; And the second a case study, because it carries out an in-depth study, elaborating the knowledge construction of the Pato Baja university project. It has exploratory nature, recommended for studies where there is little knowledge about the problem. The data source is primary and secondary. The research method is qualitative in the structuring phase of the problem and quantitative in the evaluation phase. The intervention tool used to build the performance evaluation model was the multi-criteria approach to support constructivist decision (MCDA-C) given its ability to consider the decision maker's perceptions and integrate them into a valuation model according to the project’s reality. The main results were: (i) a review and analysis of the national and international literature that allowed to build a better understanding about the research theme were made; And (ii) the performance evaluation model was constructed for the Pato Baja research project, which resulted in 98 performance indicators distributed in three major dimensions (management, production and competition). The performance profile of the current situation of the research project and the overall performance evaluation were plotted on 34 points on a scale that 0 equals the neutral level and 100 equals the good level. Additionally, improvement actions were built that would raise the overall performance of the Pato Baja research project to 51 points. Analyzing the indicators constructed in the model, with the indicators proposed by the literature, it was possible to verify that only four indicators constructed for the model of a total of 163 identified that carried out the measurement in the literature were similar, demonstrating that the model is unique, developed and valid only for the context of the Pato Baja team, reinforcing the need for a problem structuring tool. The theoretical contributions of the present study are: (i) review of the national and international literature on performance evaluation and R&D management; (ii) consolidation of the tools identified in the literature for R&D management; (iii) consolidation of the performance evaluation indicators identified in the literature for R&D management; And (iv) proposing a performance evaluation model to support the R&D management of university research projects and the collation of this with the literature.